f(x) = 5(2+x) and g(x) = x/5 +7 which maps R into R

$\displaystyle find f^{-1}x = x$

i know how to find $\displaystyle find f^{-1}x $ but am not sure what to so after that.

$\displaystyle f^{-1}x $=

y = x\5 -2

Printable View

- Dec 8th 2010, 06:49 PMsigma1function
f(x) = 5(2+x) and g(x) = x/5 +7 which maps R into R

$\displaystyle find f^{-1}x = x$

i know how to find $\displaystyle find f^{-1}x $ but am not sure what to so after that.

$\displaystyle f^{-1}x $=

y = x\5 -2 - Dec 8th 2010, 06:52 PMdwsmith
It looks like you are done. I don't see anything else you are supposed to do unless there is more to the question you didn't post. Do you need to find the inverse of g(x) too?

- Dec 8th 2010, 06:57 PMsigma1
- Dec 8th 2010, 07:02 PMdwsmith
$\displaystyle \displaystyle f^{-1}(f(x))=x$

- Dec 8th 2010, 07:12 PMsigma1
Could you show me how that is done. Am afraId I may interpret it the wrong way. Thanks.

- Dec 8th 2010, 07:14 PMdwsmith
$\displaystyle \displaystyle f^{-1}(5(2+x))=\frac{5(2+x)}{5}-2=\cdots$

- Dec 8th 2010, 07:24 PMsigma1
Ok thanks alot

- Dec 9th 2010, 01:39 AMHallsofIvy
Since you had already determined that [tex]f^{-1}(x)= \frac{x}{5}- 2, determining x such that $\displaystyle f^{-1}(x)= x$ just means solving $\displaystyle \frac{x}{5}- 2= x$.